17.1k views
5 votes
Need answer quick and simple explanation

Need answer quick and simple explanation-example-1
User GDmac
by
6.1k points

2 Answers

5 votes

Answer:

A

Explanation:

Given

(x + 2)³

= (x + 2)(x + 2)(x + 2) ← expand second/third factor using FOIL

= (x + 2)(x² + 4x + 4) ← distribute

= x(x² + 4x + 4) + 2(x² + 4x + 4) ← distribute both parenthesis

= x³ + 4x² + 4x + 2x² + 8x + 8 ← collect like terms

= x³ + 6x² + 12x + 8 → A

User Mhep
by
6.6k points
2 votes
(x + 2)(x + 2)(x + 2)
(x^2 + 4x + 4)(x + 2)
x^3 + 4x^2 + 4x + 2x^2 + 8x + 8
Simplify
Solution: x^3 + 6x^2 + 12x + 8
The answer is A

User Alokrajiv
by
5.8k points